Odpowiedzi

2009-11-22T17:39:55+01:00
1
x² + 6x + 9 - 1 = x²
x² - x² + 6x = -9 + 1
6x = - 8
x = - 8/6 = - 4/3 = - 1 i 1/3
2
2 + x² - 16 = x² - 2x + 1
x² - x² + 2x = 1 + 16 - 2
2x = 15
x = 7,5
3
x² - 4 - 2x > x² + 8
x² - x² - 2x > 8 + 4
- 2x > 12
x< - 12/2
x < -6
4
x² + 6x + 9 > x² + 6x
x² - x² + 6x - 6x > 9
0 > 9 sprzeczne
5
2x - 1< 1/2 + 1 mnożymy wszystko przez 2
4x - 2 < 1 + 2
4x < 3 + 2
x < 5/4
x < 1 i 1/4

1 5 1
2009-11-22T17:43:43+01:00
(x+3)² - 1 = x²
x²+6x+9-1=x²
6x=-8 / :6
x=-1 1/3


2+(x-4)(x+4) = (x-1)²
2+x²-16=x²-2x-1
2x=14 /:2
x=7


(x+2)(x-2) - 2x > x²+8
x²-4-2x>x²+8
-2x>12/:(-2)
x<-6


(x+3)² > x (x+6)
x²+6x+9>x²+6x
0>9


2x- 1 < 1/2 + 1
2x<1/2+1+1
2x< 1/2+ 1/2 +1/2
2x< 3/2 / :2
x< 3/2 : 2/1
x< 3/2 *1/2
x< 3/4
x< 1 1/4
2009-11-22T17:48:03+01:00
A)
(x+3)² - 1 = x²
x²+6x+9-1=x²
6x= -8/:6
x=-1⅓

b)
2+(x-4)(x+4) = (x-1)²
2+x²-16=x²-2x-1
-2x=13/:(-2)
x=6½

c)
(x+2)(x-2) - 2x > x²+8
x²-4-2x>x²+8
2x>12/:2
x>6

d)
(x+3)² > x (x+6)
x²+6x+9>x²+6x
0>-9

e)
2x- 1 < ½ + 1 /×2
4x-2<1+1
4x<4/ :4
x<1